Tanggung Jawab Perusahaan Yang Melakukan Pencemaran Lingkungan Hidup - Latuconsina, Rifqi; Angga, La Ode; Fataruba, Sabri (PATTIMURA Law Study Review, 2024)
The sustainability of living beings is an important part of life. Everyone wants to have a clean and healthy living environment. The presence of Jaya Konstruksi company as a legal subject does not carry out its obligation to compensate and take certain actions for its actions. Environmental pollution due to the company's activities that contain sand and concrete has polluted the environment around residents' homes for these actions The company must be responsible based on fault (liability based on fault).